Investigate the Optical, Structural and electrochemical properties of PVC/PMMA/NiO blend films. Issue 1 (1st March 2022) - Basappa, M; Ganesha, H; Veeresh, S; Nagaraju, Y S; Vandana, M; Vijeth, H; Devendrappa, H
Abstract: PVC/PMMA and PVC/PMMA/NiO blend films were prepared by solution casting technique. The FT-IR spectra confirms the change in the band structure and presence of hydrogen chlorine and Ni-O bond in the PVC/PMMA and NiO loaded blend film and XRD pattern reveals the formation of NiO phase in the PVC/PMMA polymer with exhibits the amorphous nature, it may increase the conductivity and stability of the material.The surface morphology shows the NiO homogeneously dispersed on the surface of PVC/PMMA matrix, and CV curve demonstrate that the rectangular shape at different scan rate from 10 mV/s to 50 mV/s. The PVC/PMMA/NiO 3% loaded polymer blend films shows the synergistic properties towards the electrochemical performance.